2019
DOI: 10.1111/and.13393
|View full text |Cite
|
Sign up to set email alerts
|

Gallic and carnosic acids improve quality of frozen‐thawed ram spermatozoa

Abstract: The objective was to determine effects of gallic acid (GA) and carnosic acid (CA), present in carob pods and rosemary extract respectively, on frozen-thawed ram spermatozoa. Thirty ejaculates were collected from five Merino rams, pooled, diluted in Tris-based extender and divided into five equal portions containing: 0.05 or 2 mM of GA; 0.05 or 0.2 mM of CA; or no additive (control). Extended semen was equilibrated at +4°C, loaded into straws, held 5 cm above liquid nitrogen for 12 min then plunged.Computer-aid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…This study observed a correlation between sperm MMP and PMI. These results are comparable to a study by Gungor et al [ 23 ] that found that gallic acid gave sperm more energy, thereby improving MMP in comparison to the control group, but resulted in a significant reduction in PMI compared to the control group. The highest percentage of high MMP was observed in sperm from the 0.5 mM Se group.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study observed a correlation between sperm MMP and PMI. These results are comparable to a study by Gungor et al [ 23 ] that found that gallic acid gave sperm more energy, thereby improving MMP in comparison to the control group, but resulted in a significant reduction in PMI compared to the control group. The highest percentage of high MMP was observed in sperm from the 0.5 mM Se group.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, they were incubated in a warm water bath (37°C for 30 minutes) in a dark room. Mitochondrial membrane potential (MMP) analysis was performed using CytExpert 2.2 software [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that CA can improve antioxidant activity in cells, inhibiting oxidative stress caused by H2O2 or other toxic substances in vivo to reduce cell damage. More importantly, CA supplementation improves the quality of thawed sperm [22]. However, whether CA has the potential to improve early embryonic development by lowering ROS levels is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it has been stated that 200 nM to 5 µM fullerene added to ram semen increases the total and progressive motility value [37]. In another study, gallic acid and carnosic acid added to ram semen were found to have the highest total motility value in gallic acid [38]. These differences are thought to be due to the added antioxidants and their doses.…”
Section: Discussionmentioning
confidence: 80%